Responsive Islamic Boarding School Management to Environmental Sustainability Through Green Pesantren Program - Kasanah, Nur; As Sajjad, Muhammad Husain; Rohmatullah, Dawam Multazamy (MUSLIM HERITAGE, 2023)
AbstractIndonesia, a country with the highest number of Islamic boarding schools in the world, is inhabited by students, all of whom carry out activities that are closely related to natural resources and impact the environment. The community as a party in direct contact should also play an active role in helping Islamic boarding schools become communities and institutions that are responsive to environmental sustainability so that all parties can realize Islam's vision, rahmatan lil'alamin. This qualitative research with a literature study approach and using descriptive analysis methods aims to analyze the efforts that can be made by Islamic boarding schools in protecting and preserving the environment and describe the role of government institutions and community organizations in supporting the Green Pesantren program. Data are obtained from laws and regulations, books, previous research results, and other sources relevant to the research purpose. The results showed that efforts to realize the Green Islamic boarding school governance regulations are: 1) management of organic and inorganic waste into goods of economic value, 2) conversion of wastewater into useful resources, 3) the use of energy-efficient green architecture-based construction, 4) saving water and electricity resources in the daily operationalization of Islamic boarding schools, and 5) efforts for renewable alternative energy as an energy source in future. The role of the community in supporting the Green Pesantren program includes 1) the Nahdlatul Ulama Alms Infak Zakat Institute (LAZISNU), Rabithah Ma'ahid Islamiyah (RMI NU), the Disaster Management and  Climate Change Institute (LPBI NU), and Bank Mega Syariah which initiated seven Islamic boarding schools as pilot projects for the  Green Pesantren program, 2) the issuance of a fatwa of the Indonesian Ulema Council Number 41 of 2014 concerning Waste Management to Prevent Environmental Damage. The results of this study are expected to be policy recommendations for the Ministry of Religious Affairs and related stakeholders to issue regulations related to the Green Pesantren program.AbstrakIndonesia sebagai negara dengan jumlah pesantren terbanyak di dunia tentunya dihuni santri yang kesemuanya tentu menjalankan aktivitas yang terkait erat dengan sumber daya alam dan berdampak pada lingkungan. Masyarakat sebagai pihak yang bersinggungan langsung seyogyanya juga berperan aktif membantu pondok pesantren menjadi komunitas dan lembaga yang responsif pada kelestarian lingkungan sehingga semua pihak dapat mewujudkan visi Islam yang rahmatan lil’alamin. Penelitian kualitatif dengan pendekatan studi kepustakaan dan menggunakan metode analisis deskripstif ini bertujuan menganalisis upaya yang dapat dilakukan pondok pesantren dalam menjaga dan melestarikan lingkungan serta mendeskripsikan peran lembaga pemerintah dan organisasi masyarakat untuk mendukung program Pesantren Hijau. Data diperoleh dari peraturan perundangan, buku, hasil riset terdahulu dan sumber lain yang relevan dengan tujuan penelitian. Hasil penelitian menunjukkan upaya untuk mewujudkan regulasi tata kelola Pesantren Hijau adalah: 1) pengelolaan sampah organik dan anorganik menjadi barang bernilai ekonomis, 2) konversi air limbah menjadi sumber daya yang bermanfaat, 3) penggunaan kontruksi berbasis arsitektur hijau yang hemat energi, 4) penghematan sumber daya air dan listrik dalam operasionalisasi pesantren sehari-hari, dan 5 pengupayaan energi alternatif terbarukan sebagai sumber energi di masa depan. Peran masyarakat dalam mendukung program Pesantren Hijau diantaranya, 1) Lembaga Zakat Infak Sedekah Nahdlatul Ulama (LAZISNU), Rabithah Ma’ahid Islamiyah (RMI NU), Lembaga Penanggulangan Bencana dan Perubahan Iklim (LPBI NU), dan Bank Mega Syariah yang menginisasi tujuh pesantren sebagai pilot project program Pesantren Hijau, 2) terbitnya fatwa Majelis Ulama Indonesia Nomor 41 Tahun 2014 tentang Pengelolaan Sampah untuk Mencegah Kerusakan Lingkungan. Hasil dari penelitian ini diharapkan dapat menjadi rekomendasi kebijakan bagi Kementerian Agama dan stakeholder terkait untuk menerbitkan regulasi terkait program Pesantren Hijau.